Within country inequalities in caesarean section rates: observational study of 72 low and middle income countries - Boatin, Adeline Adwoa; Schlotheuber, Anne; Betran, Ana Pilar; Moller, Ann-Beth; Barros, Aluisio J D; Boerma, Ties; Torloni, Maria Regina; Victora, Cesar G; Hosseinpoor, Ahmad Reza (BMJ (Online), 2018)
AbstractObjectiveTo provide an update on economic related inequalities in caesarean section rates within countries.DesignSecondary analysis of demographic and health surveys and multiple indicator cluster surveys.Setting72 low and middle income countries with a survey conducted between 2010 and 2014 for analysis of the latest situation of inequality, and 28 countries with a survey also conducted between 2000 and 2004 for analysis of the change in inequality over time.ParticipantsWomen aged 15-49 years with a live birth during the two or three years preceding the survey.Main outcome measuresData on caesarean section were disaggregated by asset based household wealth status and presented separately for five subgroups, ranging from the poorest to the richest fifth. Absolute and relative inequalities were measured using difference and ratio measures. The pace of change in the poorest and richest fifths was compared using a measure of excess change.ResultsNational caesarean section rates ranged from 0.6% in South Sudan to 58.9% in the Dominican Republic. Within countries, caesarean section rates were lowest in the poorest fifth (median 3.7%) and highest in the richest fifth (median 18.4%). 18 out of 72 study countries reported a difference of 20 percentage points or higher between the richest and poorest fifth. The highest caesarean section rates and greatest levels of absolute inequality were observed in countries from the region of the Americas, whereas countries from the African region had low levels of caesarean use and comparatively lower levels of absolute inequality, although relative inequality was quite high in some countries. 26 out of 28 countries reported increases in caesarean section rates over time. Rates tended to increase faster in the richest fifth (median 0.9 percentage points per year) compared with the poorest fifth (median 0.2 percentage points per year), indicating an increase in inequality over time in most of these countries.ConclusionsSubstantial within country economic inequalities in caesarean deliveries remain. These inequalities might be due to a combination of inadequate access to emergency obstetric care among the poorest subgroups and high levels of caesarean use without medical indication in the richest subgroups, especially in middle income countries. Country specific strategies should address these inequalities to improve maternal and newborn health.